A Comparative Study of the Properties of Zinc Ferrite Nanoparticles Synthesized by Different Techniques for Nanofluid Preparation. Issue 204 (2nd January 2020) - Sonia, L. C.; Victory, Maisnam; Phanjoubam, Sumitra
Abstract: Zinc ferrite nanoparticles have been synthesized using sol-gel and co-precipitation method. The XRD studies confirm the formation of single-phase spinel structure. The UV–visible analysis shows maximum absorption in the range of 351–398 nm. The room temperature frequency dispersion of dielectric constant, initial permeability and their corresponding loss in the range 100 Hz–1 MHz has been studied. The variation of coercivity with particle size indicates the change in domain nature from single domain to multi-domain with annealing. The as-prepared co-precipitated sample forms a more stable nanofluid indicating the suitability of co-precipitation method for nanofluid preparation.